PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP EFEKTIVITAS BANTUAN LANGSUNG TUNAI UMKM DI KECAMATAN CIBEUNYING KIDUL - Sari, Wulan; Pusparini, Nia (Jurnal Sosial Politik Unla, 2023)
In the implementation of the distribution of Direct Cash Assistance for MSME business actors in Cibeunying Kidul District, there is still distribution that is not on target, where the recipients of the assistance are not MSME business actors. Based on the problem of how much influence Policy Implementation has on Direct Cash Assistance for Micro, Small and Medium Enterprises (MSMEs). The theory used by researchers is the theory of Policy Implementation from Donal S. Van Meter and Carl E. Van Horn, namely Standards and Targets, Resources, Communication, Characteristics, Social Conditions and Disposition of Implementors. As for the Effectiveness Variable, Budiani's theoretical approach was used, namely the dimensions of Program Target Accuracy, Program Socialization, Program Objectives and Program Monitoring. Based on this theoretical approach. The research method used is quantitative with a descriptive approach. Technique The sampling used was random sampling. The data analysis technique used is simple linear regression. Based on the results of data processing, research results were obtained which showed that there was a positive and significant influence between Policy Implementation on Direct Cash Assistance for Micro, Small and Medium Enterprises (MSMEs). Thus, the research results were tested empirically. In this research, researchers also found other factors that influenced the effectiveness of the BLT UMKM program in Cibeunying Kidul District. This factor is in the Supervision variable.